The Role of Parents in the Incidence of Unintended Pregnancy in Adolescent Girls - Rahmawati, Chintya; Ningrum, Ema Wahyu; Wirakhmi, Ikit Netra (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Unintended pregnancy (UP) among adolescents is a public health issue that affects physical, psychological, and social aspects. This study aims to explore the role of parents in the incidence of UP among adolescent girls in the working area of Puskesmas Sokaraja II, Banyumas Regency. The study employed a qualitative approach with a holistic case study design. The primary informants consisted of six adolescent girls who experienced UP, while the triangulation informants were healthcare professionals handling UP cases at Puskesmas Sokaraja II. Informants were selected using purposive sampling and snowball sampling, including adolescents who experienced UP and relevant healthcare professionals. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings revealed four main themes: Permissive parenting contributes to risky behaviors due to a lack of parental supervision, limited reproductive health and sexuality education results in adolescents’ poor understanding of UP risks, low economic status restricts adolescents’ access to reproductive health services, and low self-confidence and susceptibility to environmental influences increase the risk of UP among adolescents.